2021
DOI: 10.1116/6.0001204
|View full text |Cite
|
Sign up to set email alerts
|

Properties of secondary ions in ion beam sputtering of Ga2O3

Abstract: The energy distributions of secondary ions for the ion beam sputtering of a Ga2O3 target using O2+ and Ar+ ions are measured in dependence on various process parameters using energy-selective mass spectrometry. The process parameters include sputtering geometry (ion incidence angle α, polar emission angle β, scattering angle γ), the energy of incident ions Eion, and the background pressure of O2. The main secondary ion species are identified to be Ga+, O+, O2+, and, when argon is used as a process gas, Ar+. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The IBS-Ga 2 O 3 film, which is in contact with the Ni anode, is polycrystalline and, as shown below, is semi-insulating. We believe this is due to the nature of the film deposition process [51][52][53]. It is worth noting that such relatively thick β-Ga 2 O 3 films deposited via the IBS method on UID β-Ga 2 O 3 substrates and annealed at the conditions described above are being studied for the first time.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IBS-Ga 2 O 3 film, which is in contact with the Ni anode, is polycrystalline and, as shown below, is semi-insulating. We believe this is due to the nature of the film deposition process [51][52][53]. It is worth noting that such relatively thick β-Ga 2 O 3 films deposited via the IBS method on UID β-Ga 2 O 3 substrates and annealed at the conditions described above are being studied for the first time.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…According to Refs. [51][52][53], it was expected that IBS β-Ga 2 O 3 films would be monocrystalline and of high structural quality.…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is now being applied to the ultra-wide bandgap semiconductor Ga 2 O 3 , which h is attracting interest for power electronics and solar-blind UV detectors (6)(7)(8)(9)(10). Kalanov et al (11) reported that the main secondary ions for the ion beam sputtering of Ga 2 O 3 using O + and Ar+ ions are Ga+, O+ and O2+. There is little known about the effect of FIB on the electrical and structural properties of Ga 2 O 3 , which must be rectified as this technique is integrated into process schemes for devices or TEM sample preparation.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of Ga 2 O 3 devices with promising performance have been reported. [8][9][10][11][12][13][14][15][16] In both vertical rectifiers and lateral transistor structures, the presence of residual ion beam damage after mesa isolation or milling to create fins or trenches will be detrimental to device performance, [8][9][10][11][12][13][14][15][16][17] through inducing additional leakage current or creating additional parasitics. While ion-enhanced diffusion [18][19][20][21] of point defects created on horizontal semiconductor surfaces is known to produce damage depths well beyond those expected from ion range simulations, 22,23 there is limited understanding of the damage produced on a mesa sidewall in β-Ga 2 O 3 .…”
mentioning
confidence: 99%